Assessing the recently noted surgical outcome of isolated total anomalous pulmonary venous connection repair: A single‐secondary center experience. Issue 12 (15th October 2019) - Choi, Eun‐Young; Lee, Chang‐Ha; Park, Su‐Jin; Jang, So‐Ick; Kim, Eun Sun
Abstract: Background and Aim of the Study: Total anomalous pulmonary venous connection (TAPVC) is a rare cyanotic congenital heart defect. This study aimed to evaluate the outcome of isolated TAPVC repairs and the prognoses of affected patients in the last 12 years at a single center. Methods: We retrospectively analyzed the medical records of 51 patients who underwent isolated TAPVC repair from 2007 to 2018. Results: The median age at operation was 19 days, and the median body weight was 3.3 kg. Thirteen (25.5%) patients had emergency operations, and the median follow‐up period was 29.54 ± 36.77 months. Early mortality was noted in five patients and late mortality was noted in one patient. Pulmonary vein stenosis was observed in 22 patients within 3 to 6 months after the operation, and six patients required reoperation or transcatheter interventions. Low birth weight, small left atrial volume, long operation time, and preoperative heart failure were identified as risk factors for mortality. Conclusions: Isolated TAPVC can rapidly lead to hemodynamic instability during the neonatal period and is associated with high mortality rates. Increasing the prenatal diagnosis rate and stabilizing the patients' condition before the operation are considered important for improving the surgical outcome.